Food purchasing patterns of households in a low-cost housing community implications on dietary intake - Cabotaje, Luzviminda M. (1983)
An investigation of some household characteristics and food shopping practices was undertaken among 141 households in a low-cost housing community in Diliman, Queszon City. The food expenditure patterns of a sub-sample of thirty-nine households using a seven-day record of food bought and consumed was likewise determined. Variations were noted on household characteristics, food shopping practices and expenditure patterns. Some food shopping practices such as preparations made before shopping was significantly related to household characteristics such as: homemaker's educational level, monthly household income, food expense per day and food storage facilities. Reading of labels of canned/packed foods was related to housewife's educational level while frequency of buying perishable foods was significantly related to food storage facility. Evaluation of the seven-day record of food bought and consumed showed a per capita food expense per day of P5.63. Two-thirds of this food expenditure was alloted to fish, meat and poultry, and cereals and cereal products. Determination of adequacy in terms of the recommended allowances for the different food groups showed that cereals and cereal products, sugar; other fruits and vegetables, meat, fish and poultry, milk and milk products and fats and oil were adequate while eggs, dried beans and nuts, vitamin C rich foods, starchy roots and tubers and green leafy and yellow vegetables were inadequate. The nutrient contribution of these food groups was adequate for calories, protein and niacin and inadequate for calcium, vitamin A, thiamine, riboflavin and vitamin C. The average food expenditure of the households was found to be adequate in meeting the recommendations for the different food groups using a simple mathematical equation. Moreover, a lesser food expenditure can be made. Per capita food cost was found to be highly correlated with the adequacy of the nine essential nutrients.